2016
DOI: 10.3390/nu8120824
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Milk Consumption and the Risk of Cognitive Disorders

Abstract: The association between milk intake and cognitive disorders has been investigated in several epidemiological studies, but the findings are still conflicting. No quantitative assessment has been performed to evaluate the potential relationship of milk intake and cognitive disorders. From the inception to October 2016, the PubMed and the Embase databases were searched for observational studies reporting the association of milk consumption and cognitive disorders (Alzheimer’s disease, dementia, and cognitive decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 36 publications
1
38
0
1
Order By: Relevance
“…A recent meta-analysis among 10,940 participants shows that the higher consumption of milk was significantly associated with cognitive disorders. Compared with people with lowest level of milk consumption, people at the highest level of milk consumption had a decrease in cognitive disorders of 28% ( 35 ). The benefit of consuming milk in slowing the cognitive decline may be attributed to its protein, minerals, vitamins, and essential amino acids ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis among 10,940 participants shows that the higher consumption of milk was significantly associated with cognitive disorders. Compared with people with lowest level of milk consumption, people at the highest level of milk consumption had a decrease in cognitive disorders of 28% ( 35 ). The benefit of consuming milk in slowing the cognitive decline may be attributed to its protein, minerals, vitamins, and essential amino acids ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with people with lowest level of milk consumption, people at the highest level of milk consumption had a decrease in cognitive disorders of 28% ( 35 ). The benefit of consuming milk in slowing the cognitive decline may be attributed to its protein, minerals, vitamins, and essential amino acids ( 35 , 36 ). Although Chinese dietary guidelines present the benefit of consuming milk, our previous study showed that milk was consumed by an extremely small proportion of older people, with only 0.5% of them meeting the recommended intake of dairy ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two other cohort studies of Australian men and French women found that regular consumers of full-cream milk was associated with poorer cognitive function assessed by MMSE (23) and higher intakes of dairy desserts and ice-cream was associated with cognitive decline (24). A meta-analysis involving a total of 10,941 participants from four cohort studies and three cross-sectional studies concluded that there is an inverse relationship between milk consumption and cognitive disorders (Alzheimer's disease, dementia, and cognitive decline/impairment) but this was limited to Asian participants who are noted to have relatively lower intake of overall milk and dairy products (14). Milk consumption is relatively low among Singaporeans (34), as it is among Japanese, which reinforces the evidence that among Asians, high dairy intake reduced the risk of MCI or dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, there were reports suggesting that consumption of sh with high level of n-3 polyunsaturated fatty acids (PUFAs) may be protective against the risk of dementia but this was not consistently supported by other studies (7)(8)(9)(10)(11)(12)(13). More recently, emerging evidence suggest an association between consumption of dairy products and cognitive disorders, but the ndings are also mixed (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). While some researchers have reported that lower intake of milk is signi cantly associated with increased risk of cognitive disorders (16)(17)(18)(20)(21)(22), other studies did not support the inverse association (19,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…It is intriguing that CSN1S1 is biologically related to the Apolipoprotein E (APOE) and Clusterin (CLU) genes (Table 2), which have been shown to delay ADAOO in PSEN1 E280A mutation carriers and as a mediator of Aβ toxicity with neuroprotective effects, respectively [5,35,44]. Epidemiological studies suggest that intake of milk and fermented dairy products are significantly associated with a decreased risk of AD, cognitive decline, and cognitive-related disorders in the elderly [45][46][47][48][49]. A mouse model of AD fed with camembert cheese, which was obtained from sterilized milk fermented with Lactococcus lactis to reduce the pH and subsequently with Penicillium candidum, showed both significantly reduced levels of amyloid β (Aβ) accumulation and hippocampal inflammation, and enhancing hippocampal neurotrophic factors [50].…”
Section: Discussionmentioning
confidence: 99%